Pemodelan Virtual Reality Studi Kasus Pengenalan Laboratorium Komputer Universitas Indraprasta - Dudi Parulian; Sri Mardiyati (Jurnal Informatika Universitas Pamulang, 2021)
Utilization of information technology can be applied in many fields, one of which is the field of education. One of the tools in the field of education is a building that supports teaching and learning activities. Buildings in educational activities have many forms and facilities, one of which is a computer laboratory building at Indraprasta University. The laboratory building for new students requires more complete information because it includes many facilities. Utilizing information technology in the form of virtual reality to describe the laboratory building helps new students get to know more about the facilities owned by the university. Introduction of virtual reality laboratories to new students with Virtual Reality. The object displayed is the model and layout of the Laboratory. By using Sketchup, Unity, and Android Studio with the Android platform. Researchers created a simple Virtual Reality application that is easy to use. This application displays Virtual Reality computer laboratory objects along with the laboratory information. This application can be used in several versions of Android smartphones such as 4.1.1 and above.